The Role Of BAPAS In Implementing Diversion In Cases Of Persecution By Children - Permana, Bintang Johan; Neri Widya Ramailis (Sisi Lain Realita, 2023)
BAPAS (Correctional Center) is a Technical Implementation Unit of the Ministry of Law and Human Rights at the Directorate General of Corrections. BAPAS (Correctional Center) has the task of guiding clients, in this case aiming to realize the reintegration of previously prisoners back into the community environment without any negative stigma or rejection in society. As for the role of BAPAS (Correctional Center) in the implementation of diversion in cases of persecution by children, namely, in the form of assistance, guidance, and supervision. The purpose of the study is to determine the role of BAPAS (Correctional Center) in the implementation of diversion in cases of persecution by children based on the role theory coined by Robert Linton. The research method used in this research is qualitative research method. Data collection techniques through observation, interviews, and documentation studies. The problem studied in this research is the role of BAPAS (Correctional Center) in the implementation of diversion in cases of persecution by children guided by Law No.11 of 2012 concerning the Child Criminal Justice System. The results of this study indicate that the role of BAPAS (Correctional Center) in the implementation of diversion in cases of persecution by children has been effective and instrumental. This is evidenced by assistance, guidance, and supervision by BAPAS (Correctional Center) and observations, interviews, and documentation studies conducted. The role of BAPAS (Correctional Center) in implementing diversion in cases of persecution by children has been able to achieve its goal of realizing restorative justice.